How to deal with pain in the emergency department - pain management review - Beutler, Katarzyna; Bijata, Bartosz; Burek, Dawid; Paszkowska, Aleksandra; Kujawa, Aleksandra; Matuszewska, Urszula; Nykowska, Aleksandra (Journal of Education, Health and Sport, 2024)
One of the primary health issues bringing patients to hospital emergency rooms is pain. It is often treated inadequately. Doctors working in the emergency department have the option of using a number of drugs for analgesia. The three main groups include non-steroidal anti-inflammatory drugs, non-opioid analgesics and opioid analgesics. In order to properly exploit their potential, it is necessary to properly classify the pain, know the basic action of the available drugs, choose the right dose, and know how to combine drugs from different groups to achieve balanced analgesia. By acting in this way, the patient in the hospital emergency department will be properly provided with medication, and this will have a positive effect on his overall health.